Predisposing factors for failure of conservative treatment in umbilical pilonidal sinus: A clinical experience (Annals of Medical Research, 2021)
Aim: Pilonidal sinus is a chronic inflammatory disease that occurs in the sacrococcygeal region; but also occurs in the umbilical region. Conservative and surgical treatment methods have been used for management of umbilical pilonidal sinus. Aim of this study was to evaluate the risk factors for failure of conservative treatment.Materials and Methods: Between June 2016 and March 2018, 16 patients diagnosed with umbilical pilonidal sinus in our clinic were evaluated retrospectively. The demographical and clinical data, interventions, complications and follow-up results of the patients were recorded.Results:All of 16 patients initially treated conservatively. After conservative treatment, pilonidal sinus excision was performed to 7 (43.75%) patients; five (31.25%) of that patients had no regression of symptoms and two (12.5%) of them had recurrence. Personal history of umbilical pilonidal sinus, dark skin color, deep navel, and poor personal hygiene were found as predisposing factors for failure of conservative treatment.Conclusion: Although there is no consensus in the treatment of umbilical pilonidal sinus; the first treatment approach should be conservative. It should be kept in mind response to conservative management could be poor in patients with the predisposing factors.
Keywords: Pilonidal sinus; umbilical region; conservative treatment.